Factors Influenced the Instilling of Islamic Values at Islamic Boarding School - Firman, Firman; Anam, Sholih Khudin (SYAMIL: Journal of Islamic Education, 2021)
Islamic boarding schools as educational institutions play a role to build  Islamic values. Islamic values are patterns or concepts that are upheld by Muslims with various main problems related to Islam. This type of research was qualitative descriptive research that was the process of research by conducting an assessment of phenomena, and events, in the life of students, by directly or indirectly involved in the settings studied. The main problem in this research is how factors influence the cultivation of Islamic values in Islamic boarding schools. The purpose of the research was to examine the factors that influence the cultivation of Islamic values on students at the Islamic Boarding School of Hidayatullah Balikpapan. The methods of collecting data were conducted by observations, interviews, and documentation through researchers collecting data step by step and then concluded. The process of processing and analyzing data through three analysis activities simultaneously, namely: (1) data reduction (2) data display, (3) and concluding. The results of the research showed that the factors of cultivating Islamic values to students at the Islamic boarding school of Hidayatullah Balikpapan were (1) the integration of curriculum, (2) integrated between mosques, dormitories, and madrasah in the educational process, (3) the existence of qudwah (role model) from elders, community leaders, alumni, and seniors, (4) the support of the government and the local community. Meanwhile, Islamic values were instilled from the aspect of religion, worship, and morality.